(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This article looks at the impact of right wing and left-wing political radicalism, feminist, suburban sprawl, and publicly education institutionalization and reformation on the homeschool phenomenon in the United States. It then goes on to clarify how the movement, which included components from both the left and right in the early 1980s, colluded to battle agressive legal environments in numerous nations, but were eventually taken over by conservative Presbyterians in the late 1980s due to its superior to their outstanding organization and numerical dominance. Despite internal disagreement, the movement’s goals of regulating and publicising homeschooling have been met by the mid-1990s. Since then, schooling has grown in prominence and is increasingly being adopted by more mainstream segments of society, often in conjunction with public schools, hinting that the term "homeschooling" as a political organization and ideology may have outlived its use.